Policy environment for prevention, control and management of cardiovascular diseases in primary health care in Kenya - Asiki, Gershim (BMC Health Serv Res, 2018)
BACKGROUND: In Kenya, cardiovascular diseases (CVDs) accounted for more than 10% of total deaths and 4% of total Disability-Adjusted Life Years (DALYs) in 2015 with a steady increase over the past decade. The main objective of this paper was to review the existing policies and their content in relation to prevention, control and management of CVDs at primary health care (PHC) level in Kenya. METHODS: A targeted document search in Google engine using keywords “Kenya national policy on cardiovascular diseases” and “Kenya national policy on non-communicable diseases (NCDs)” was conducted in addition to key informant interviews with Kenyan policy makers. Relevant regional and international policy documents were also included. The contents of documents identified were reviewed to assess how well they aligned with global health policies on CVD prevention, control and management. Thematic content analysis of the key informant interviews was also conducted to supplement the document reviews. RESULTS: A total of 17 documents were reviewed and three key informants interviewed. Besides the Tobacco Control Act (2007), all policy documents for CVD prevention, control and management were developed after 2013. The national policies were preceded by global initiatives and guidelines and were similar in content with the global policies. The Kenya health policy (2014–2030), The Kenya Health Sector Strategic and Investment Plan (2014–2018) and the Kenya National Strategy for the Prevention and Control of Non-communicable diseases (2015–2020) had strategies on NCDs including CVDs. Other policy documents for behavioral risk factors (The Tobacco Control Act 2007, Alcoholic Drinks Control (Licensing) Regulations (2010)) were available. The National Nutrition Action Plan (2012–2017) was available as a draft. Although Kenya has a tiered health care system comprising primary healthcare, integration of CVD prevention and control at PHC level was not explicitly mentioned in the policy documents. CONCLUSION: This review revealed important gaps in the policy environment for prevention, control and management of CVDs in PHC settings in Kenya. There is need to continuously engage the ministry of health and other sectors to prioritize inclusion of CVD services in PHC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-018-3152-4) contains supplementary material, which is available to authorized users.